Understanding the Culture of 4-H - Marilyn N. Norman; Joy C. Jordan (EDIS)
Webster defines culture as the concepts, habits, skills, arts, instruments, and institutions of a given people in a given place. Basically, the culture within a group is what everybody knows that everybody else knows and includes the visible expression as well as the invisible roots of the culture. Most groups have spoken or unspoken expectations for member’s behavior. These may include rules, rituals, language, demonstration of support for commonly held beliefs, etc. Youth development professionals know the importance of helping young people discover quickly the norms of the group they have joined. This document is 4-HS FS101.1, one of a series of the Florida 4-H Program, UF/IFAS Extension. Published May 2006.